Development of an E-Handout Based on Discovery Learning on The Reaction Rate for Class XI Students - Nurul Faudia; Ajat Sudrajat; Nurfajriani Nurfajriani (Jurnal Akademika Kimia, 2025)
This study aims to determine the level of feasibility, practicality, and the students' readability response to e-handout-based discovery learning. This development research uses 4-D development models developed by S. Thiagarajan, Dorothy S. Semmel, and Melvin 1 Semmel. The 4-D development model has four stages: the Define stage, the Design stage, the Development stage, and the Disseminate stage, but this study is limited to 3-D: the Define stage, the Design stage, and the Development stage. The subjects in this study were 3 material experts and media experts, five chemistry subject teachers, and the readability response of MIPA 1 class XI students, with 33 people. Data collection instruments include an interview sheet, an e-handout assessment sheet by a material expert validator and a media expert, a practicality sheet by a teacher, and a student reading response sheet. Data analysis techniques use qualitative and quantitative data. Based on the results of the study, an analysis of the needs of students showed that students agreed that it was necessary to develop an e-handout based on discovery learning on the reaction rate material. Then, assessment by material expert validators of an 85% well-deserved e-handout, assessment by media expert validators of an 86% well-deserved e-handout, teacher practicability of an 88% well-deserved or very practical e-handout, and 87% of students' readability response to e-handouts is said to be very decent or very high.